The UK and the conflict in Ukraine - Robert Hudson (University American College Skopje, 2022)
The focus of this paper will be on the role played by post-"Brexit", "Global Britain" in the face of the continuing conflict in Ukraine. Emphasis will be placed upon the background of public opinion and the current political climate in the UK and on how Britain's role on the international scene has changed significantly since the 'Brexit' referendum of 2016 whereby, for some commentators, the conflict in Ukraine has even provided the UK government with a rare opportunity and success in foreign policy, especially in the aftermath of the chaotic withdrawal from Kabul in August 2021.
Keywords: 330; Ukrainian refugees; UK public opinion; Post-"Brexit" foreign policy; and Homes for Ukraine